2017
DOI: 10.1007/s10096-017-2988-6
|View full text |Cite
|
Sign up to set email alerts
|

Increase of circulating endocan over sepsis follow-up is associated with progression into organ dysfunction

Abstract: How circulating inflammatory mediators change upon sepsis progression has not been studied. We studied the follow-up changes of circulating vasoactive peptides and cytokines until the improvement or the worsening of a patient and progression into specific organ dysfunctions. In a prospective study, concentrations of tumor necrosis factor-alpha (TNFα), interleukin (IL)-6, IL-8, IL-10, interferon-gamma (IFNγ), endocan and angiopoietin-2 (Ang-2) were measured in serum by an enzyme immunoassay in 175 patients at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…Endocan is a vasoactive and endothelial-derived molecule that is mainly produced in the event of ARDS. Since previous studies have also associated this biomarker with the progression of septic patients into organ dysfunction [ 14 ], it is not surprising that levels greater than 13 ng/ml are predictive for failure to withdrawal from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocan is a vasoactive and endothelial-derived molecule that is mainly produced in the event of ARDS. Since previous studies have also associated this biomarker with the progression of septic patients into organ dysfunction [ 14 ], it is not surprising that levels greater than 13 ng/ml are predictive for failure to withdrawal from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies have shown elevated plasma endocan concentrations in patients with sepsis [ 12 ] and have associated them with disease severity and progression [ 13 ]. Other studies have identified plasma endocan levels as an independent predictor in septic patients progressing into ARDS [ 14 ] and have explored its potential as a biomarker to predict disease severity and mortality in ARDS [ 15 ]. Nonetheless, the full value of endocan as a biomarker and the significance of its levels in the endothelial lining fluid (ELF) in ARDS have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells play a key role in the pathogenesis of sepsis by producing cytokines and chemotactic agents, and by expressing surface adhesion molecules, which induce migration of circulating leukocytes into tissues. Indeed, both endocan and angiopoietin-2 are endothelial-specific biomarkers which increase during sepsis, worsening into multiple organ dysfunction syndrome (MODS), and decrease when sepsis improves [ 47 ]. Endocan showed correlation with VCAM-1 and E-selectin but not with ICAM-1 [ 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…A total of 446 patients with or without ARDS at ICU admission have been tested currently for endocan. In polytrauma, severe sepsis, or septic shock patients without ARDS at admission, high levels of endocan were found predominantly in patients who did not develop ARDS [ 47 , 56 58 ]. Consistently, blood endocan levels below 5.5 ng/ml in these critically ill patients without ARDS at admission were associated with a high risk of ARDS occurrence within 3 days (Table 4 ).…”
Section: Main Textmentioning
confidence: 99%
“…Endocan, a DS-PG synthesized and secreted by endothelial cells, is metabolized mainly by proteases throughout the lung and by inflammatory cells. Endocan levels are increased in the serum of patients with ARDS, pneumonia, and septic shock, and any increase of this PG in serum is a surrogate marker of worsening clinical course towards organ dysfunction [17,18]. Thus, analysis of PG fragments from the basal membrane of the alveolar epithelium and endothelium and from the interstitium might be helpful in the near future as early phase markers of lung injury in previously uninjured or injured lungs.…”
Section: The Ecm and Ventilator-induced Lung Injurymentioning
confidence: 99%